COVIDifying Education through the Lens of Award-Winning Educators in a State University in the Philippines (European Journal of Teaching and Education, 2021)
Paradigm shifts in the field of education have been an issue in the Philippines since the COVID-19 pandemic struck. To fill this gap, this study sought to highlight the pedagogical practices and teaching experiences of award-winning educators in a State University. The qualitative data extracted from semi-structured interviews were analyzed following a thematic analysis based on descriptive phenomenology. One finding revealed that the educators’ years in service and educational attainments were helpful in their migration from face-to-face to distance education, even though the number of course preparations was a weight on their shoulders. Secondly, the educators conducted their classes through preparation and implementation via fifteen instructional methods, formative and summative assessments, and feedback. On another note, the educators determined six roadblocks in their teaching practice with explanations on how they overcame them. Amidst all these, they mentioned that it is imperative to uphold empathy in the conduct of their classes.